Baduy Customary Law Pluralism in the Legal Framework of the Indonesian Constitution: Towards Fair Governance - Hendrawati, Sulkiah; Saepudin, Eli Apud (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The pluralism of Baduy customary law is a constitutional reality within the Indonesian constitutional system, particularly regarding the recognition of indigenous communities. The existence of Baduy customary law influences local governance, which is based on local wisdom, customary adherence, and social sustainability. However, the harmonization of customary law and state law often faces normative and implementation challenges. Purposes of the Research: This study aims to analyze the pluralism of Baduy customary law within the framework of Indonesian constitutional law and its implications for just governance. The research focuses on the form of constitutional recognition, the relationship between state authority and customary institutions, and the contribution of Baduy customary law in realizing the principles of justice, legal certainty, and respect for the rights of indigenous peoples contextually, normatively, and empirically within Indonesia's current modern and diverse regional government system. Methods of the Research: The research method used is qualitative research with a normative juridical and sociolegal approach. Data were obtained through a library study of laws and regulations, court decisions, and scientific literature, supported by empirical data from previous studies. Data analysis was conducted descriptively and analytically to interpret the relationship between Baduy customary law and the principles of constitutional law and the Indonesian constitution, values ​​of justice, pluralism, customary recognition, and the practice of sustainable, adaptive, contextual, democratic, and national local governance. Results of the Research: The research findings indicate that Baduy customary law holds a strategic position within the national legal system through conditional constitutional recognition. The novelty of this research lies in the assertion that customary legal pluralism does not conflict with constitutional law, but rather enriches the concept of just governance. The integration of Baduy customary values ​​supports the principles of substantive justice, community participation, and respect for collective customary rights. These findings emphasize the need for adaptive constitutional policies policies based on the values ​​of the Indonesian constitution to ensure harmony between customary law and the state in a sustainable, inclusive, democratic, contextual, national, modern, responsive, just, dignified, balanced, participatory, and constitutionally oriented manner.